2016
DOI: 10.3892/ol.2016.4492
|View full text |Cite
|
Sign up to set email alerts
|

Optimal settings and accuracy of indocyanine green fluorescence imaging for sentinel node biopsy in early gastric cancer

Abstract: Abstract. Indocyanine green (ICG) fluorescence imaging represents a promising method for sentinel node (SN) biopsy in laparoscopic gastric surgery due to its signal stability. In the present study, the suitability and optimal settings of ICG fluorescence imaging for SN biopsy in early gastric cancer were determined. Patients with single primary superficial-type adenocarcinoma of the stomach, lesions <5 cm in diameter, and no evident nodal metastasis and out of indication for endoscopic submucosal dissection we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 40 publications
(71 reference statements)
2
71
0
2
Order By: Relevance
“…Of the 13 studies that were all submitted from Japan, 7 combined ICG with infrared ray electronic endoscopy (IREE), 2 combined with infrared ray laparoscopic system (IRLS), and 4 combined with fluorescence imaging (FI) system. As a novel technique, the FI method involved Infrared Camera System PDE, PDE‐2, and PDE neo …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 13 studies that were all submitted from Japan, 7 combined ICG with infrared ray electronic endoscopy (IREE), 2 combined with infrared ray laparoscopic system (IRLS), and 4 combined with fluorescence imaging (FI) system. As a novel technique, the FI method involved Infrared Camera System PDE, PDE‐2, and PDE neo …”
Section: Resultsmentioning
confidence: 99%
“…Recently developed intraoperative FI systems are able to provide simultaneous acquisition of surgical anatomy and fluorescence signal . Even SLNs that were not stained green with ICG could be clearly visualized by the bright fluorescence . Other studies reported that the FI system allowed more clear and bright visualization than NIR imaging .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3). ICG fluorescence imaging enables the easy visualization of SNs and will replace the SN mapping method in many malignancies including gastric cancer [15][16][17]. Subsequently, a laparoscopic gamma probe introduced from the trocar port is used to locate the radioactive SN.…”
Section: Laparoscopic Sn Mapping Proceduresmentioning
confidence: 99%
“…As a result, the number of SNs in early gastric cancer is generally five to eight nodes (1,3,4). The lymphatic basins are thought to be the primary lymphatic drainage area in each patient, and patients with gastric cancer often have two or three basins (1,(3)(4)(5). The authors need to take sufficient time for detection of and decisions about the SNs and lymphatic basins, while dyeing all of the direct nodes.…”
mentioning
confidence: 99%